The Square Curve Paradigm for Research in Alternative, Complementary, and Holistic Medicine: A Cost-Effective, Easy, and Scientifically Valid Design for Evidence-Based Medicine and Quality Improvement - Soren Ventegodt; Niels JØrgen Andersen; Joav Merrick (The Scientific World Journal)
In this paper we present a new research paradigm for alternative, complementary, and holistic medicine — a low-cost, effective, and scientifically valid design for evidence-based medicine. Our aim is to find the simplest, cheapest, and most practical way to collect data of sufficient quality and validity to determine: (1) which kinds of treatment give a clinically relevant improvement to quality of life, health, and/or functionality; (2) which groups of patients can be aided by alternative, complementary, or holistic medicine; and (3) which therapists have the competence to achieve the clinically relevant improvements. Our solution to the problem is that a positive change in quality of life must be immediate to be taken as caused by an intervention. We define “immediate” as within 1 month of the intervention. If we can demonstrate a positive result with a group of chronic patients (20 or more patients who have had their disease or state of suffering for 1 year or more), who can be significantly helped within 1 month, and the situation is still improved 1 year after, we find it scientifically evidenced that this cure or intervention has helped the patients. We call this characteristic curve a “square curve”. If a global, generic, quality-of-life questionnaire like QOL5 or, even better, a QOL-Health-Ability questionnaire (a quality-of-life questionnaire combined with a self-evaluated health and ability to function questionnaire) is administered to the patients before and after the intervention, it is possible to document the effect of an intervention to a cost of only a few thousand Euros/USD. A general acceptance of this new research design will solve the problem that there is not enough money in alternative, complementary, and holistic medicine to pay the normal cost of a biomedical Cochrane study. As financial problems must not hinder the vital research in nonbiomedical medicine, we ask the scientific community to accept this new research standard.